Quantifying postural stability of patients with cerebellar disorder during quiet stance using three-axis accelerometer. (February 2018) - Adamová, Barbora; Kutilek, Patrik; Cakrt, Ondrej; Svoboda, Zdenek; Viteckova, Slavka; Smrcka, Pavel
Highlights: Quantifying postural stability of patients with cerebellar disorder during stance. Quantifying postural stability of quiet stance using 3-D accelerometer. Data were obtained by the IMU compared with data obtained by force platform. The three-axis accelerometer evaluates all three coordinates of a movement. A pathological balance control has been identified by IMU and force platform. Abstract: This work focuses on the novelty of applying a 3-D postural analysis on the cerebellar disorders diagnosis and on introduction of an alternative to recent methods of quantifying the human postural stability during quiet stance, which uses a three-axis accelerometer. It introduces an advantage in the form of an ability to evaluate a complex three-dimensional (3-D) movement, as opposed to a major limitation of todaýs alternatives that evaluate only two coordinates in space. 3-D data (anterior-posterior, superior-inferior, and medio-lateral accelerations of a patient́s trunk) were obtained using a three-axis accelerometer (Xsens Mtx), enabling us to evaluate 3-D translational body movements on the basis of the average velocity (AV) of the point and the total length (TL) of the 3-dimensional trajectory. Then a pathological balance control has been identified from the 3-D plot of the three trajectories. The data were obtained from patients suffering from the progressive cerebellar ataxia as well as from healthy participants and were analyzed statistically. The analysis revealed several significant differences between the AVs and TLs of the patients versus the healthy participants.